Effects of metamizole, MAA, and paracetamol on proliferation, apoptosis, and necrosis in the pancreatic cancer cell lines PaTu 8988 t and Panc-1 - Manuela Malsy; Bernhard Graf; Anika Bundscherer (BMC, 2017)
Abstract Background Adenocarcinoma of the pancreas is one of the most aggressive cancer diseases affecting the human body. Recent research has shown the importance of the perioperative phase in disease progression. Particularly during this vulnerable phase, substances such as metamizole and paracetamol are given as general anesthetics and postoperative analgesics. Therefore, the effects of metamizole and paracetamol on tumor progression should be investigated in more detail because the extent to which these substances influence the carcinogenesis of pancreatic carcinoma is still unclear. This study analyzed the influence of metamizole and its active metabolites MAA (4-N-methyl-aminoantipyrine) and paracetamol on the proliferation, apoptosis, and necrosis of the pancreatic cancer cell lines PaTu 8988t and Panc-1 in vitro. Methods Cell proliferation was measured by means of the ELISA BrdU assay and the rate of apoptosis by flow cytometry using the Annexin V assay. Results Metamizole and paracetamol significantly inhibited cell proliferation in pancreatic cancer cells. After the addition of metamizole to PaTu 8988t cells, the rate of apoptosis was reduced after 3 h of incubation but significantly increased after 9 h of incubation. Conclusion The oncogenic potential of pancreatic adenocarcinoma is mainly characterized by its extreme growth rate. Non-opioid analgesics such as metamizole and paracetamol are given as general anesthetics and postoperative analgesics. The combination of metamizole or paracetamol with cytotoxic therapeutic approaches may achieve synergistic effects. Further studies are necessary to identify the underlying mechanisms so that new therapeutic options may be developed for the treatment of this aggressive tumor.